(untitled) (Zaporizhzhia Historical Review, 2021)
The genesis of Don Cossackhood and different ethnic communities taking part in the process are the object of the given research. The author concludes, that despite the prominent historiographic tradition, this problem still lacks special complex investigation. In the last 60 years a reductive approach to the problem has been applied that is a remarkable backward step even in comparison with the archievements of the end of XIX – beginning of XXth century.